2015
DOI: 10.2500/ajra.2015.29.4121
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous CSF Rhinorrhea: Prevalence of Multiple Simultaneous Skull Base Defects

Abstract: A significant number of patients with spontaneous CSF rhinorrhea may have more than one skull base defect present at the time of presentation. The clinical significance of this finding in surgical and medical decision making is not clear at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 11 publications
0
19
0
1
Order By: Relevance
“…The pathogenesis of CSF rhinorrhea is unclear, but previous studies have hypothesized that prolonged ICH may lead to defects in the skull base over time. These defects coupled with ICH can cause herniation of the dura mater into the bony defects, weakening the dura mater and making it more prone to dural tears and thus leading to a dural-mucosal fistula [5]. Similarly, obesity causes increased intra-abdominal pressure, leading to the elevation of the diaphragm and thereby leading to increased pleural and cardiac pressures, thus decreasing venous return from the brain to the heart and causing ICH [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of CSF rhinorrhea is unclear, but previous studies have hypothesized that prolonged ICH may lead to defects in the skull base over time. These defects coupled with ICH can cause herniation of the dura mater into the bony defects, weakening the dura mater and making it more prone to dural tears and thus leading to a dural-mucosal fistula [5]. Similarly, obesity causes increased intra-abdominal pressure, leading to the elevation of the diaphragm and thereby leading to increased pleural and cardiac pressures, thus decreasing venous return from the brain to the heart and causing ICH [3,6].…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have identified several potential risk factors for this syndrome such as elevated body mass index (BMI), obstructive sleep apnea (OSA), and intracranial hypertension [ 3 6 ]. Although the exact pathogenesis of spontaneous CSF rhinorrhea is not known, investigators have speculated that defects in the skull base may develop as a result of elevated intracranial pressures [ 7 ]. One explanation is that individuals who have a predisposition to this syndrome and develop intracranial hypertension may spontaneously form a dural-mucosal fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Through this defect, the dura may herniate and form meningoceles or, if the defect is big, the cerebral parenchyma can also herniate through (encephalocele) 8 . A study conducted by Lieberman et al on patients with spontaneous CSF rhinorrhea proved that they had multiple simultaneous bony defects in the skull base 4 . The researchers found that intracranial hypertension represents a determining factor for the appearance of these defects.…”
Section: Spontaneous Csf Leaksmentioning
confidence: 99%
“…The underlying condition that leads to CSF discharge into the nasal cavities is the disruption of the limits between the rhinosinusal cavities and the anterior and middle cerebral fossae. The communication with the central nervous system may determine multiple infectious complications, with high morbidity and potentially severe patient outcome 3,4 . Most frequently, we encounter CSF leaks in the anterior cerebral fossa, because it has the most sites of congenital weakness and also the sites that are related to the specific surgery type.…”
Section: Pathophysiologymentioning
confidence: 99%